Factors associated with early-onset neonatal sepsis in children of peruvian military personnel. - Mogollón, C.A. (2019)
Introduction: The risk factors for early-onset neonatal sepsis (EOS) are well known. However, they have still not been evaluated in children of military personnel, which are a special population. Objective: To determine factors associated with EOS in children of Peruvian military personnel in a hospital. Materials and Methods: This is an observational, analytical, and retrospective study that included neonates hospitalized in the Neonatal Unit of the Hospital Militar Central, Peru between 2009 and 2017. Data were compiled from clinical history and hospital stay records. Sepsis cases were cross-checked against other variables of interest via generalized linear models. Results: Out of a total of 2,371 included neonates, 114 neonates were diagnosed with EOS. There was an increased frequency of neonatal sepsis with longer neonatal hospital stay (adjusted prevalence ratio (aPR): 1.21; 95% confidence interval (CI): 1.15–1.28; p<0.001), greater gestational age (aPR: 1.03; 95% CI: 1.01–1.05; p =0.003), and development of urinary tract infection in pregnant women in the third trimester of pregnancy (aPR: 2.27; 95% CI: 1.39–3.73; p=0.003). In contrast, there was a lower incidence of neonatal sepsis in female neonates (aPR: 0.64; 95% CI: 0.42–0.99; p=0.044). Conclusions: The associated factors with EOS in children of Peruvian military personnel were sex, longer neonatal hospital stay, gestational age and development of urinary tract infection in pregnant women during the third trimester of pregnancy. The aforementioned information is significant in describing this neonate population.